Different Immunoregulation Roles of Activin A Compared With TGF-β - Li, Fanglin; Long, Yiru; Yu, Xiaolu; Tong, Yongliang; Gong, Likun (Frontiers in Immunology, 2022)
Activin A, a critical member of the transforming growth factor-β (TGF-β) superfamily, is a pluripotent factor involved in allergies, autoimmune diseases, cancers and other diseases with immune disorder. Similar to its family member, TGF-β, activin A also transmits signals through SMAD2/SMAD3, however, they bind to distinct receptors. Recent studies have uncovered that activin A plays a pivotal role in both innate and adaptive immune systems. Here we mainly focus its effects on activation, differentiation, proliferation and function of cells which are indispensable in the immune system and meanwhile make some comparisons with those of TGF-β.